Promising Antiproliferative Compound From the Green Microalga Dunaliella tertiolecta Against Human Cancer Cells - Martínez, Kevin A.; Saide, Assunta; Crespo, Gloria; Martín, Jesús; Romano, Giovanna; Reyes, Fernando; Lauritano, Chiara; Ianora, Adrianna (Frontiers in Marine Science, 2022)
Dunaliella tertiolecta is a green flagellated microalga with a high tolerance to salinity and high production of pigments such as zeaxanthin, a xanthophyll carotenoid present in higher plants known for its antioxidant potential. In the current study, the antiproliferative activity of raw extracts and fractions of D. tertiolecta (clone CCMP 1320) was evaluated against four different human cancer cell lines: melanoma, hepatocellular liver carcinoma, and two lung adenocarcinoma cell lines. In addition, a normal cell line (lung fibroblast) was used as toxicity control. The activity was evaluated by treatment with the extracts/fractions following the MTT colorimetric assay procedures. HPLC-UV-HRMS based dereplication helped to identify the bioactive metabolites. A glycoglycerolipid and the pigment crocoxathin were identified in the active fraction and might be involved in the bioactivity of this microalga. The compound glycerol 1-(9Z,12Z,15Z-octadecatrienoate)-2-(4Z,7Z,10Z,13Z-hexadecatetraenoate)-3-O-β-D-galactopyranoside (1) was purified and its antiproliferative activity was confirmed. This work gives new insights on the antiproliferative activity of the green alga D. tertiolecta and its potential industrial applications.